Crystal structure of KPC-2: insights into carbapenemase activity in Class A β-lactamases - Ke, Wei (2007)
β-lactamases inactivate β-lactam antibiotics and are a major cause of antibiotic resistance. The recent outbreaks of Klebsiella pneumoniae carbapenem-resistant (KPC) infections mediated by KPC type β-lactamases are creating a serious threat to our “last resort” antibiotics, the carbapenems. KPC β-lactamases are thus carbapenemases and are a subclass of Class A β-lactamases that have evolved to efficiently hydrolyze carbapenems and cephamycins which contain substitutions at the α position proximal to the carbonyl group that normally render these β-lactams resistant to hydrolysis. To investigate the molecular basis of this carbapenemase activity, we have determined the structure of KPC-2 at 1.85Å resolution. The active site of KPC-2 reveals the presence of a bicine buffer molecule which interacts via its carboxyl group with conserved active site residues S130, K234, T235, and T237; this likely resembles the interactions the β-lactam carboxyl moiety makes in the Michaelis-Menten complex. Comparison of the KPC-2 structure with non-carbapenemases and previously determined NMC-A and SME-1 carbapenemase structures shows several active site alterations that are unique among carbapenemases. An outward shift of the catalytic S70 residue renders the active sites of the carbapenemases more shallow likely allowing easier access of the bulkier substrates. Further space for the α-substituents is likely provided by shifts in N132 and N170 in addition to concerted movements in the postulated carboxyl binding pocket that might allow the substrates to bind in a slightly different angle to accommodate these α-substituents. The structure of KPC-2 thus provides key insights into the carbapenemase activity of emerging Class A β-lactamases.